2010
DOI: 10.1177/0265407510381255
|View full text |Cite
|
Sign up to set email alerts
|

Student–teacher relationships and students’ willingness to seek help for school violence

Abstract: Students’ willingness to seek help from a teacher to deal with four different forms of violence (physical, relational, verbal, and use of weapon) was studied. The role of positive teacher–student relationships and whether such relationships mediate students’ perceptions of the teacher’s ability to assist were assessed. Findings pointed to only partial mediation in physical, relational, and verbal violence and no mediation in the case of weapon use. Girls and younger students were more willing to seek help for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 44 publications
(76 reference statements)
2
21
0
Order By: Relevance
“…When considering student demographics, several notable patterns were found. First, age was not associated with school attachment and school safety but was associated with help‐seeking, which is consistent with prior evidence indicating younger children may be more likely to seek help (Kochenderfer‐Ladd & Pelletier, ; Kristensen & Smith, ; Yablon, ). While gender did not moderate the relationship between either form of victimization and school safety, gender differences were found for school attachment and help‐seeking.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…When considering student demographics, several notable patterns were found. First, age was not associated with school attachment and school safety but was associated with help‐seeking, which is consistent with prior evidence indicating younger children may be more likely to seek help (Kochenderfer‐Ladd & Pelletier, ; Kristensen & Smith, ; Yablon, ). While gender did not moderate the relationship between either form of victimization and school safety, gender differences were found for school attachment and help‐seeking.…”
Section: Discussionsupporting
confidence: 85%
“…A child's gender may be a salient factor to consider in understanding victimization experiences and perceptions of school climate. For example, studies indicate that girls are more likely than boys to seek help in response to peer victimization (Kristensen & Smith, ; Tenenbaum, Varjas, Meyers, & Parris, ; Unnever & Cornell, ; Yablon, ). Furthermore, research indicates that boys are more likely to experience peer victimization in a physical form (Carbone‐Lopez, Esbensen, & Brick, ; Crick & Bigbee, ; Crick & Nelson, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Berlan et al (2010) found that these teens are more likely to report bullying than heterosexual teens. Yablon (2010) conducted a study with 313 secondary school students utilizing vignettes to establish student-teacher connectedness. The study found that whether or not a student reported bullying and allowed adult intervention was mediated by the quality of the student-teacher relationship.…”
mentioning
confidence: 99%